The euro and the consumer as political phenomena in the current development of Europe (2014)
The capitalist economic systemis not getting off worldwidesince 2008. Soitseems that political institutions should try to finda new legal frame work for economic relations. One question remains unanswered until today: if legal guarantees shall be subject to the economic systemor, other wise, the economy shall be permeated by the prevalence of the rights and liberties of the individual? In order to do a first approach to any answers, we should ponder the understanding of the new economic pattern of a transnational market, for example the Euro, with the new concept of legal subject in the same market, that is, the consumer. This article tries tocover this idea in the European Union framework.